Different Foot Positioning During Calf Training to Induce Portion-Specific Gastrocnemius Muscle Hypertrophy - Nunes, João Pedro; Costa, Bruna D V; Kassiano, Witalo; Kunevaliki, Gabriel; Castro-E-Souza, Pâmela; Rodacki, André L F; Fortes, Leonardo S; Cyrino, Edilson S (Journal of strength and conditioning research, 2020)
Nunes, JP, Costa, BDV, Kassiano, W, Kunevaliki, G, Castro-e-Souza, P, Rodacki, ALF, Fortes, LS, and Cyrino, ES. Different foot positioning during calf training to induce portion-specific gastrocnemius muscle hypertrophy. J Strength Cond Res 34(8): 2347-2351, 2020-The aim of this study was to compare the changes in gastrocnemius muscle thickness (MT) between conditions such as which foot was pointed outward (FPO), foot was pointed inward (FPI), or foot was pointed forward (FPF). Twenty-two young men (23 ± 4 years) were selected and performed a whole-body resistance training program 3 times per week for 9 weeks, with differences in the exercise specific for calves. The calf-raise exercise was performed unilaterally, in a pin-loaded seated horizontal leg-press machine, in 3 sets of 20-25 repetitions for training weeks 1-3 and 4 sets for weeks 4-9. Each subject's leg was randomly assigned for 1 of the 3 groups according to the foot position: FPO, FPI, and FPF. Measurements with a B-mode ultrasound were performed to assess changes in MT of medial and lateral gastrocnemius heads. After the training period, there were observed increases in MT of both medial (FPO = 8.4%, FPI = 3.8%, and FPF = 5.8%) and lateral (FPO = 5.5%, FPI = 9.1%, and FPF = 6.4%) gastrocnemius heads, and significant differences for magnitude of the gains were observed between FPO and FPI conditions (p < 0.05). Positioning FPO potentiated the increases in MT of the medial gastrocnemius head, whereas FPI provided greater gains for the lateral gastrocnemius head. Our results suggest that head-specific muscle hypertrophy may be obtained selectively for gastrocnemius after 9 weeks of calf training in young male adults.